First application of GammaTile cesium-131 brachytherapy with maximal safe resection of a glioma in a patient with limited scleroderma - Pasli, Melisa; Cowles, Sara; Jo, Jasmin; Yaqoub, Mahmoud; Kanaan, Hilal A.; Ju, Andrew W.; Peach, Sean (Journal of Contemporary Brachytherapy, 2023)
The purpose of this report is to present the first documented application of GammaTile to an intra-cranial tumor of a patient with a symptomatic radiosensitive connective tissue disorder, a case where there were significant concerns with standard oncologic strategies. We hypothesized that GammaTile ® (GT Medical Technologies, Tempe, Arizona, USA) would also be advantageous in the application of intra-cranial tumors in patients with conditions of increased radiosensitivity. We generated a standard external beam radiation therapy (EBRT) plan consisting of an overall 1.5 cm expansion to 59.4 Gy in 1.8 Gy fractions. Also, we developed a CyberKnife (Accuray, Sunnyvale, CA, USA) plan with a 5 mm expansion on the surgical cavity prescribed to 60 Gy in 30 fractions, to make an EBRT comparison using the same prescription volume as GammaTile. We report the first published application of GammaTile ® brachytherapy to an intra-cranial malignancy in a patient with limited scleroderma. The dose delivered by GammaTile was compared to the dose that would be delivered with both typical volumes and small volumes of EBRT. The maximum dose delivered to the scar and scalp by GammaTile was reduced to half of that from other external beam techniques ( ~ 25 Gy vs. ~ 55 Gy). MRI imaging at 6 months and 12 months post-resection demonstrated no evidence of disease recurrence nor radiation necrosis. At the 12-month follow-up visit, the surgical scar was well-healed with no skin changes to the surrounding scalp. Dosimetrically and clinically, this report highlights the successful application of GammaTile to an intra-cranial tumor bed in a patient with scleroderma.